Temporal and spatial characterization of keratinocytes supporting orf virus replication - Byung-Joon Seung; Sushil Khatiwada; Daniel L. Rock; Gustavo Delhon (Frontiers in Cellular and Infection Microbiology)
Reflecting their tropism for keratinocytes, most poxviruses that infect vertebrates replicate to high titers and cause pathology in the skin. Keratinocytes, the main cells of the epidermis, are found in different stages of a differentiation program that produces the critical barrier against environmental damage. While systemic poxviruses (e.g. smallpox virus, sheeppox virus) also infect other cell types, the parapoxvirus orf virus (ORFV), which causes localized infections in sheep and goats, has not been shown to replicate in cells other than keratinocytes. Notably, ORFV infection only occurs after or concomitant with epidermal damage and the subsequent healing response and shows unexplained delayed virus replication in an uncharacterized keratinocyte subpopulation. Using in situ hybridization, immunohistochemistry, confocal microscopy, qPCR, and a full-thickness wound/infection model in sheep, the natural host, we show that during an initial 2-day eclipse phase viral transcription and viral DNA replication are not detected. Between days 2 and 3 pi, viral transcription is first detected in keratinocytes of the stratum granulosum and upper stratum spinosum in the proliferative zone at the wound margin. These cells are positive for cytokeratin 10, a suprabasal marker; cytokeratin 6, a protein induced during early repair responses; stratum granulosum markers filaggrin and loricrin; and negative for the nuclear proliferation marker Ki-67 and cytokeratin 14, a basal cell marker. This marker profile suggests that keratinocytes supportive of viral replication are engaged in advanced keratinocyte differentiation rather than proliferation.